Extended lead(II) architectures engineered via tetrel bonding interactions; New Journal of Chemistry; Vol. 42, iss. 7 - Mahmoudi G. Ghodrat; Zangrando E. Ennio; Mitoraj M. P. Mariusz; Gurbanov A. V. Atash; Moosavifar M. Maryam; Zubkov F. I. Fedor; Konyaeva I. A. Irina Aleksandrovna; Kirillov A. M. Alexander; Safin D. A. Damir (2018, 2018)
Title screen